Peningkatan Motivasi dan Keterampilan Menulis Eksplanasi dengan Menggunakan Metode Peer Teaching - Ahmad Salim; Sumarwati Sumarwati; St. Y Slamet (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2019)
Abstract: Writing is a skill about pouring an idea or concept in form of write (written). The research conducted in the XI TKR 4 class off SMK NU Ma'arif Kudus showed that the value of the student writing skill is still low. This research purpose is to raise a writing skills by using the peer teaching method. This research was conducted from April to March. The subjects in this study were teachers and students of class XI TKR 4 of SMK NU Ma'arif Kudus. Data in the form of photos, videos, lesson plans, test results, lists of values, notes on interview results and field notes. Data sources include: informants, places and events, and documents. The validity of the data uses triangulation method and triangulation data source. Data analysis techniques use critical analysis techniques and comparative descriptive techniques. Indicator of achievement is 80%. Research procedures consist of planning, implementing actions, and reporting. In cycle I their learning motivation was in the moderate category, namely 53,12%, in cycle II it was in the high category, namely 78,12. The attainment of explanation writing competence in cycle I 68,75% of the students attained the MMC, in cycle II 90,62% of the students attained the MMC. The results of the study showed that the application of the peer teaching method was able to improve the explanatory writing skills of students in class XI TKR 4 SMK NU Ma'arif Kudus.